THE IMPORTANCE OF CULTURE IN THE SOCIETY ENVIRONMENT - Hudaya, Sania Sauma Rizky; Najla, Reifa; Anaztasya, Raditha (Jurnal Kopendik, 2023)
Culture plays a central role in forming identity, strengthening social relationships, and influencing human interactions with the natural and social environment around them. Through culture, people develop a deep understanding of themselves and recognize their role in the social context. Cultural norms and values play an important role in shaping healthy and harmonious social behavior and relationships. Culture also has the ability to maintain and preserve the natural environment through local wisdom and sustainable practices. Apart from that, culture is also a source of creativity and expression for individuals and groups in society. The importance of culture in society is also reflected in its ability to adapt and change over time. Societies that are open to the influence of other cultures can adopt and adapt new elements, allowing them to thrive and survive in the face of social and environmental change. In order to maintain, appreciate and develop culture, communities need to continue to preserve their cultural heritage and promote intercultural understanding and tolerance. Thus, the importance of culture in society not only includes aspects of identity and social relations, but also makes an important contribution to economic development, social development and environmental preservation. In writing this article, it is intended that readers can add insight through reading the article. This article was written using the literature study method. Includes the meaning of culture in the community, elements of culture, the nature of culture, and the importance of culture in the community.